Methodical Aspects of Indirect Assessment of Household Incomes in Determining the Eligibility for Government Social Support - Sarioglo, V. Н. (Statistics of Ukraine, 2020)
In present-day Ukraine, a large number of families and individuals are beneficiaries of programs for social support of the population. Economic and political crises, reforms in tariff and social policies, added by the pandemic of coronavirus infection in the latest time, result in the worsening life standards of a considerable share of the population in certain periods of time. In was in 2015–2018 that in some of the quite populated localities social programs covered as many as 70% of the population. This triggered a respective growth in the social support from the central and local budgets. Such situation aggravated the problem of targeting of the government social support, decreasing the number of cases when a social aid is assigned in an improper or baseless manner, and the scopes of fraud in this sphere. One of the ways for reforming the system of social support in the present days is to adopt the method of assigning all the categories of support with consideration of incomes and property status of applicants. The property status of families or individuals can be quite accurately measured given the access to the registers containing data on houses, land plots, transport vehicles etc. either possessed or disposed by them. However, given a high level of employment in the informal sector, large scales of the shadow economy and external labor migration, assessment of the actual income level of families constitutes a serious problem. Quite often the stated incomes do not correspond with actual ones, and applicants do not have stimuli to disclose their real life standards. The article’s objective is to expose a methodological approach to operational assessment of potential incomes of applicants and recipients of social support. Approaches based on statistical models of correlation between life standards and sets of households’ or individuals’ characteristics have been constructed and used in many developing countries where the conditions for formation of the population incomes are similar to the ones in Ukraine. The article highlights methodological foundations for building up the models for operational assessment of the population income, with due account to issues of information support to modeling and use of income assessment results. Examples of computations by the proposed models are given.